Features of histological structure and differential diagnostics of the diffuse-type giant cell tumor and its malignant form. - Dyadyk, E. A.; Hryhorovska, A. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Tenosynovial giant cell tumor of diffuse type is one of the most widespread tumor of joints, causing destruction of the soft tissues and bone articular surfaces. Objective. The purpose of the study was to formulate approaches to histological differential diagnostics between diffuse-type giant cell tumor and its malignant forms. Methods. Tissues of 40 biopsies and resected foci of the affected joints and tendon sheaths from patients with diagnosis Tenosynovial giant cell tumor of diffuse type or malignant giant cell tumor. Results. Important diagnostic signs of malignancy are cellular atypia, such as changed histological architectonics, high mitotic activity, the areas of necrosis, prevalence of the increased cellularity with spindling forms and hyperchromic nuclei in mononuclear component. Our experience of histologic diagnostics confirms that diffuse-type giant cell tumor without obvious evidences of malignancy usually possesses 2-4 significant diagnostic signs for its differentiation with the malignant form of the given tumor. Conclusion: Practice of histologic differential diagnostics reveals considerable difficulties of interpretation of histologic features of diffuse-type giant cell tumor. Thus, further research and specification of criteria for its differential diagnostics are relevant.